2021
DOI: 10.3390/educsci11090467
|View full text |Cite
|
Sign up to set email alerts
|

Combining Project Based Learning and Cooperative Learning Strategies in a Geotechnical Engineering Course

Abstract: This paper presents the implementation of a learning methodology following a student-centred approach. The methodology is based on the use of project based and cooperative learning and mainly consists of commissioning students to prepare a presentation on a topic of their subject. Students work in groups, and later must deliver a real lecture to their colleagues. The proposed methodology was applied across 7 years and its implementation was monitored via day-to-day observations, annual surveys, the gathering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A few educators and researchers have also combined TEL with project-based learning, problem-based learning, and cooperative learning in GEE. In this regard, the application of TEL with project-based learning, which involves students working on design projects that require them to apply the knowledge and skills they have learned in class, is growing in popularity in GEE [3]. With the help of this method, students gain real-world experience, develop problem-solving abilities, and become better-equipped to handle the demands of the workplace.…”
Section: Trends Of Technology-enhanced Learning In Geotechnical Engin...mentioning
confidence: 99%
See 1 more Smart Citation
“…A few educators and researchers have also combined TEL with project-based learning, problem-based learning, and cooperative learning in GEE. In this regard, the application of TEL with project-based learning, which involves students working on design projects that require them to apply the knowledge and skills they have learned in class, is growing in popularity in GEE [3]. With the help of this method, students gain real-world experience, develop problem-solving abilities, and become better-equipped to handle the demands of the workplace.…”
Section: Trends Of Technology-enhanced Learning In Geotechnical Engin...mentioning
confidence: 99%
“…TEL offers geotechnical engineering students access to diverse learning resources, i.e., computer-aided design tools, virtual reality simulations, and online resources that can help them visualize and analyze geotechnical problems in a more interactive and intuitive manner. Additionally, TEL can provide geotechnical engineering students with real-life scenarios that they can use to apply their knowledge and skills, which can help them establish critical thinking and problem-solving skills that are the core requirement for learning [3]. By means of TEL, geotechnical engineering students can learn more proficiently, engage more vigorously with the course content, and gain a deeper understanding of geotechnical engineering problems, which can eventually prepare them for success in their careers as geotechnical or civil engineers.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are pedagogical strategies, approaches, cooperative learning, learner-to-learner interaction during the lessons, frequent assessment, technology integration, and timeous feedback. Mitra and Crawley (2014), Phage (2018), andTorrijo et al (2021) found that learners' conceptual understanding is enhanced when they learn collaboratively and cooperatively rather than when they learn as individuals. Torrijo et al's (2021) finding is in line with Hadwin et al's (2011) socially shared regulated learning (SSRL) theory and Vygotsky's (1968) social constructivism, which view social interaction as a precondition to effective physical sciences learning.…”
Section: Conceptual Understandingmentioning
confidence: 99%
“…One of the learning models that offer learner-centered activities is the project-based learning model (Ngereja et al, 2020). In line with this, (Torrijo et al, 2021) suggests that project-based learning has become a pedagogical learning which starts to be widely used in the implementation of learning in universities. This project-based learning assigns learners to complete one or more tasks that produce meaningful learning outcomes or products.…”
Section: Introductionmentioning
confidence: 98%